Peran Lanjut Usia dalam Masyarakat dan Keluarga pada Pemberdayaan Lanjut Usia di Kelurahan Lesanpuro Kota Malang - Atika Safira Ramadhani; I Wayan Suwena; Aliffiati Aliffiati (Department of Anthropology Udayana University, 2020)
Lesanpuro sub-district is one of the sub-districts in Malang where has an old population structure with a percentage of 15.56% of the population being elderly. 60% of the total elderly are young elderly with an age range of 60-69 years old, while the rest are elderly with the age over 70 years old. The elderly in Lesanpuro sub-district are elderly who still carry outvarious kinds of daily activities, such as activities related to hobbies and religions, to taking part in the community activities. By still carrying out various activities in old age, reflects the empowerment done by the elderly in order to actualize themselves. Therefore, this research was conducted to know the role of elderly in the society and family and the implications of the role of the elderly for society and the family so that they can help the elderly to achieve the goal of empowerment, which is self-actualization. This research uses a qualitative descriptive approach and is expected to reveal the existing phenomena based on facts and events that occurs in the field.